Predicting the limits: Tailoring unnoticeable hand redirection offsets in virtual reality to individuals' perceptual boundaries - FEICK, Martin (Institutional Knowledge at Singapore Management University, 2024)
Many illusion and interaction techniques in Virtual Reality (VR) rely on Hand Redirection (HR), which has proved to be effective as long as the introduced offsets between the position of the real and virtual hand do not noticeably disturb the user experience. Yet calibrating HR offsets is a tedious and time-consuming process involving psychophysical experimentation, and the resulting thresholds are known to be affected by many variables—limiting HR’s practical utility. As a result, there is a clear need for alternative methods that allow tailoring HR to the perceptual boundaries of individual users. We conducted an experiment with 18 participants combining movement, eye gaze and EEG data to detect HR offsets Below, At, and Above individuals’ detection thresholds. Our results suggest that we can distinguish HR At and Above from no HR. Our exploration provides a promising new direction with potentially strong implications for the broad field of VR illusions.